Effect of lattice constant on band-gap energy and optimization and stabilization of high-temperature In xGa 1 -xN quantum-dot lasers - Humayun, M. A.; Md Abdur Rashid, Dr.; Mohd Fareq, Abd. Malek, Dr.; A. N. Hussain (Springer US, 2013)
Link to publisher's homepage at http://link.springer.com/